Sinterhardening Process of Lean Cr-Mo Prealloyed Steel for Moderately Loaded Applications - Koblik, Dmitriy; Ťavodová, Miroslava; Vargová, Monika; Hnilica, Richard; Náprstková, Nataša (Manufacturing Technology Journal, 2025)
The article deals with sinterhardening process of lean Cr-Mo prealloyed steel for moderately loaded applications. New material Astaloy CrS with low alloying volume of chromium and molybdenum was analyzed as possible basis for sinterhardening process. Standard mechanical properties of frequently used and more expensive materials such as DistaloyDH and Astaloy CrM are chosen as a compara-tive criterion. Astaloy CrS+0.85%C samples with different compaction densities and Ni content were studied, mechanical properties and hardness after sinterhardening process were compared. The influ-ence of additional high-temperature sintering on mechanical properties was assessed. The micro-structure of the sinterhardening (SH) and high-temperature sintering + sinterhardening (HTS+SH) samples was studied quantitative analysis of the phase was given. As result, tensile strength greater than 900 MPa and hardness greater than 33 HRC can be obtained for investigated material.
Keywords: Sintering; High-temperature sintering; Astaloy CrS; Density; Microstructure